Answer: ⇒ [tex]=2a-5x-3[/tex]
____________________________________________
Step-by-step explanation:
First you had to expand.
[tex]-5(x-3)=-5x+15[/tex]
[tex]=-5x+15+2(a-9)[/tex]
Then you had to expand again.
[tex]2(a-9)=2a-18[/tex]
[tex]=-5x+15+2a-18[/tex]
Simplify it's should be the right answer.
[tex]-5x+15+2a-18=2a-5x-3[/tex]
_____________________________________________________
Hope this helps!
Thank you for posting your question at here on brainly.
Have a great day!
________________________________________________________